The role of Zic genes in inner ear development in the mouse: Exploring mutant mouse phenotypes. Issue 11 (16th September 2014) - Chervenak, Andrew P.; Bank, Lisa M.; Thomsen, Nicole; Glanville‐Jones, Hannah C.; Jonathan, Skibo; Millen, Kathleen J.; Arkell, Ruth M.; Barald, Kate F.
<x xml:space="preserve">Abstract</x> Background: Murine Zic genes (Zic1–5) are expressed in the dorsal hindbrain and in periotic mesenchyme (POM) adjacent to the developing inner ear. Zic genes are involved in developmental signaling pathways in many organ systems, including the ear, although their exact roles haven't been fully elucidated. This report examines the role of Zic1, Zic2, and Zic4 during inner ear development in mouse mutants in which these Zic genes are affected. Results:Zic1/Zic4 double mutants don't exhibit any apparent defects in inner ear morphology. By contrast, inner ears from Zic2kd/kd and Zic2Ku/Ku mutants have severe but variable morphological defects in endolymphatic duct/sac and semicircular canal formation and in cochlear extension in the inner ear. Analysis of otocyst patterning in the Zic2Ku/Ku mutants by in situ hybridization showed changes in the expression patterns of Gbx2 and Pax2. Conclusions: The experiments provide the first genetic evidence that the Zic genes are required for morphogenesis of the inner ear. Zic2 loss‐of‐function doesn't prevent initial otocyst patterning but leads to molecular abnormalities concomitant with morphogenesis of the endolymphatic duct. Functional hearing deficits often accompany inner ear dysmorphologies, making Zic2 a novel candidate gene for ongoing efforts to identify the genetic basis of human hearing loss. Developmental Dynamics 243:1487–1498, 2014. © 2014 Wiley Periodicals, Inc.